Non-Cross-Linked Collagen Mesh Performs Best in a Physiologic, Noncontaminated Rat Model. (June 2019) - Kaufmann, Ruth; Jairam, An P.; Mulder, Irene M.; Wu, Zhouqiao; Verhelst, Joost; Vennix, Sandra; Giesen, Louis J. X.; Clahsen-van Groningen, Marian C.; Jeekel, Johannes; Lange, Johan F.
Background . In laparoscopic incisional hernia repair, direct contact between the prosthesis and abdominal viscera is inevitable and may lead to adhesions. Despite the large variety of mesh prosthesis, little is known about their in vivo behavior. Biological meshes are considered to have many advantages, but due to their price they are rarely used. A rat model was used to assess biological and conventional synthetic meshes on their in vivo characteristics. Design . One-hundred twenty male Wistar rats were randomized into five groups of 24 rats. A mesh was implanted intraperitoneally and fixated with nonresorbable sutures. The following five meshes were implanted: Parietene (polypropylene), Permacol (cross-linked porcine acellular dermal matrix), Strattice (non-cross-linked porcine acellular dermal matrix), XCM Biologic (non-cross-linked porcine acellular dermal matrix), and Omyra Mesh (condensed polytetrafluoroethylene). The rats were sacrificed after 30, 90, or 180 days. Incorporation, shrinkage, adhesions, abscess formation, and histology were assessed for all meshes. Results . All animals thrived postoperatively. After 180 days, Permacol, Parietene, and Omyra Mesh had a significantly better incorporation than Strattice ( P = .001, P = .019, and P = .037 respectively). After 180 days, Strattice had significantly fewer adhesions on the surface of the mesh than Parietene ( P < .001), Omyra Mesh ( P = .011), and Permacol ( P = .027). After 30 days, Permacol had significantly stronger adhesions than Strattice ( P = .030). However, this difference was not significant anymore after 180 days. After 180 days, there was significantly less shrinkage in Permacol than in Strattice ( P = .001) and Omyra Mesh ( P = .050). Conclusion . Based on incorporation, adhesions, mesh shrinkage, and histologic parameters, Strattice performed best in this experimental rat model.